Lead Generation for Human Mitotic Kinesin Eg5 Using Structure-based Virtual Screening and Validation by In-vitro and Cell-based Assays - Makala, Himesh; Alexandar, Soundarya P.; Nagarajan, Devipriya; Mahapatra, Santanu Kar; Ulaganathan, Venkatasubramanian (Current Computer - Aided Drug Design, 2021)
Background: Human mitotic kinesins play a crucial role in mitotic cell division. Targeting the spindle separation phase of mitosis has gained much attention pharmaceutically in cancer chemotherapy. Spindle segregation is carried out mainly by Eg5 kinesin, and currently, it has many inhibitors in different phases of clinical trials. All the current drug candidates bind un-competitively with ATP/ADP at allosteric site 1 (formed by loop L5, helix α2 and helix α3). Recent experiments show that inhibitors that bind to the site 2 (formed by helix α4 and helix α6) are either competitive or uncompetitive to ATP/ADP. Objectives: To identify suitable lead compounds that target the mitotic kinesin Eg5, using in silico screening and their validation using in vitro and cell-based assays. Methodology: Potential inhibitors were screened for human Eg5 (kinesin-5) through structurebased virtual screening and the top-scoring compounds were validated using steady-state ATPase assay, differential scanning fluorimetry, and microscale thermophoresis. The anti-cancer activity of the compounds was evaluated in the epithelial (A549) and chronic myelogenous leukemia (K562) cancer cell lines. A known strong binding inhibitor, S-trityl-L-cystine, is used as a reference compound. Results: Out of the many compounds tested, MM01 and MM03 showed good cell-based activity against the cancer cell lines A549 and K562 and can be further studied in animal models. Conclusion: In this study, a structure-based approach was used to identify the potential inhibitors and validate them using different in-vitro and cell-based assays.
Keywords: Eg5